Effect of AR gene-specific knockout on the process of radiation-induced pulmonary fibrosis and its mechanism: AR gene-specific knockout in RIPF - Zhang, Ziyu; Li, Zepeng; Chen, Xiao; Wang, Yinhua; Li, Xianwei (Cellular and Molecular Biology, 2023)
Numerous studies have proved that epithelial-mesenchymal transition (EMT) of lung epithelial cells is one of the important causes of radiation-induced pulmonary fibrosis (RIPF). Aldose reductase (AR) is a monomer enzyme in the polyglycolic metabolic pathway and belongs to the aldo-keno reductase protein superfamily. Our previous studies have found that AR as one of the most significantly up-regulated genes was associated with the development of bleomycin-induced PF in rats. It is not clear whether aldose reductase is related to the regulation of radiation-induced EMT and mediates RIPF. AR-knockout mice, wild-type mice and lung epithelial cells were induced by radiation to establish a RIPF animal model and EMT system, to explore whether AR is mediation to RIPF through the EMT pathway. In vivo, AR deficiency significantly alleviated radiation-induced histopathological changes, reduced collagen deposition and inhibited collagen I, matrix metalloproteinase 2 (MMP2) and Twist1 expression. In addition, AR knockout up-regulated E-cadherin expression and up-regulated α-SMA and Vimentin expression. In vitro, AR, collagen I and MMP2 expression were increased in lung epithelial cells after radiation, which was accompanied by Twist1 expression up-regulation and EMT changes evidenced by decreased E-cadherin expression and increased α-SMA and Vimentin expression. Knockdown or inhibition of AR inhibited the expressions of Twist1, MMP2 and collagen I, and reduced cell migration and reversed radiation-induced EMT. These results indicated that aldose reductase may be related to radiation-induced lung epithelial cells EMT, and that inhibition of aldose reductase might be a promising treatment for RIPF.